APPLICATION OF WAKALAH CONTRACT TO GOODS DELIVERY SERVICES - Fuadi; Muhammad Ramadhan; Chuzaimah Batubara (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
This study aims to determine the application of the wakalah contract to goods delivery services (case study on goods delivery services in Bireuen Regency). This research uses primary data obtained by interviewing company leaders and consumers. In this study, the research subjects are company leaders and consumers. The results of this study indicate that the application of the wakalah contract to the delivery of goods has been applied in the Bireuen Regency area, and has fulfilled the elements of the provisions of the wakalah contract seen from the company's work procedures, but regarding delays in delivery of goods, damage to goods and loss of goods the company will be responsible by providing compensation according to the classification of losses if consumers follow according to company procedures.